Preparation and characterization of FsHA/FsCol beads: cell attachment and cytotoxicity studies - Ismail Zainol (Tanjung Malim, 2023)
Preparation and characterization of FsHA/FsCol beads: cell attachment and cytotoxicity studies by Ismail Zainol